NILAI MORAL DAN KEARIFAN LOKAL DALAM PEPACCUR LAMPUNG: KAJIAN SOSIOLOGI SASTRA - Jimny, Zahra Adellia Dewi; ZR, Mutiara Ananda; Prayogi, Rahmat; Widodo, Mulyanto (STKIP Pesisir Selatan, 2025)
Objective: Abstract This study aims to uncover the moral values and forms of local wisdom contained in Pepaccur, a form of oral literature of the Lampung people that serves as a medium for conveying advice, communication, and social ethical guidelines. Using a qualitative descriptive method with a sociology of literature approach, this study examines several Pepaccur texts obtained through documentation and interviews with cultural practitioners. The analysis focused on identifying the moral values emerging in these oral expressions and their relationship to the Lampungnese philosophy of life, Piil Pesenggiri. The results reveal that Pepaccur encompasses moral values of piety to God, politeness, social solidarity, and wisdom in social interactions. These values reflect elements of local wisdom such as nemui nyimah (love), nengah nyappur (grace), sakai (grace), and juluk adek (dear sister), which serve as ethical guidelines for the Lampung people in maintaining social harmony and order. Thus, Pepaccur is not only a form of oral art but also a cultural representation that serves to preserve and transmit moral values between generations